2017
DOI: 10.1177/1535370217699537
|View full text |Cite
|
Sign up to set email alerts
|

Changes in duodenal enteroendocrine cells in patients with irritable bowel syndrome following dietary guidance

Abstract: Several contributing factors to the symptomology of irritable bowel syndrome (IBS) have been identified, such as abnormal densities of enteroendocrine cells and diet; however, the interactions between these factors have not been studied yet. The current study aims at exploring the dynamic changes between these two factors by studying the effect of using low fermentable oligo-, di-, monosaccharides and polyol (FODMAP) diet (known to improve IBS symptoms) through dietary guidance on the enteroendocrine cell dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
1
9
0
1
Order By: Relevance
“…At the cellular level, changing the diet through individual dietary guidance changes the densities of different GI endocrine cells in different parts of the GI tract ( 172 175 ), as shown in Figs. 2 – 5 .…”
Section: Individual Dietary Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, changing the diet through individual dietary guidance changes the densities of different GI endocrine cells in different parts of the GI tract ( 172 175 ), as shown in Figs. 2 – 5 .…”
Section: Individual Dietary Guidancementioning
confidence: 99%
“…For example, in the stomach, the densities of several endocrine cells (gastrin, ghrelin, serotonin and somatostatin) changed toward the values measured in healthy control subjects after providing dietary guidance, but only somatostatin cell density showed a significant change in the gastric corpus ( 181 ). The densities of serotonin cells in the duodenum and ileum changed significantly ( 172 , 175 ), and the density of somatostatin cells in the duodenum changed significantly after providing dietary guidance toward that measured in healthy control subjects ( 175 ). After providing dietary guidance, the densities of serotonin and PYY cells tend to normalize in different segments of the colon, with the density of somatostatin cells increasing in the rectum ( 174 ).…”
Section: Individual Dietary Guidancementioning
confidence: 99%
“…Interactions of the above-mentioned contributing factors with each other have certain effects on the gut-brain axis that may contribute to the development of symptoms related to the gastrointestinal [9,10] and nervous [11,12] systems. Previous publications have shown the effect of dietary changes on the symptoms [1,[13][14][15][16], gut microbiota [17,18], and enteroendocrine cells [19][20][21] in IBS patients. In addition, changing the composition of the gut microbiota through fecal microbiota transplantation (FMT) had a positive clinical outcome not only in cases of Clostridium difficile [22,23] but also in IBS [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…3. Single somatostatin-immunoreactive NEC found in the small intestine of control (C2) and experimental (HR group) animals by dietary guidance (24). In rats with experimentally induced colitis, the numbers of somatostatin-IR NEC were significantly lower than they were in the controls (12).…”
Section: Resultsmentioning
confidence: 92%
“…Additionally, it has also been demonstrated that increased numbers of serotonin NEC in the small intestine mucosae accompany several gastrointestinal disorders, such as celiac disease (25), refractory celiac disease (9), and inflammatory bowel disease (32). In the course of inflammatory bowel disease, a proper diet can change the number of NEC to normal (24). It is known that the main action of intestinal serotonin is to promote local inflammation.…”
Section: Resultsmentioning
confidence: 99%